PATHOLOGIC FINDINGS IN 36 SLOTHS FROM BRAZIL - Arenales, Alexandre; Silva, Fabiana Lessa; Miranda, Flavia; Brandao Guedes, Paula Elisa; Werther, Karin [UNESP]; Loyola Teixeira da Costa, Maria Elvira; Tinoco, Herlandes Penha; Coelho, Carlyle Mendes; Santos, Renato Lima (Amer Assoc Zoo Veterinarians, 2020)
Sloths are xenarthrans from Central and South America with a highly adapted morphophysiology. Five of the six known species of sloths are found in Brazil, among which Bradypus torquatus (maned three-toed sloth) is considered a vulnerable species by International Union for Conservation of Nature. Nevertheless, knowledge on health and disease of sloths is very scarce, thus this study aimed to describe macroscopic and microscopic findings in 36 Brazilian sloths. The most common findings included iron storage disorder, probable bacterial pneumonia, gastric and intestinal nematode parasitism, and a presumptive diagnosis of systemic mastocytosis.